Experimental and Theoretical Study of Thermodynamics and Transport Properties of Multilayer Polymeric Food Packaging - Guarda-Moraga, A; Romero-Figueroa, J; Galotto-Lopez, M; Torres-Mediano, A (2012)
The specific migration of Octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (I-1076) from three-layer low-density polyethylene plastic films into a fatty food simulant was studied. The film samples, having a symmetrical structure with a contaminated core layer and virgin outer layers, were developed with a known amount of a selected migrant in the inner layer. A phenomenological model based on a resistances-in-series was resolved through the regula falsi algorithm according to a routine that considers the income of the structural parameters of the system and experimental conditions in which migration testing was performed. The model s accuracy in predicting migration was demonstrated successfully by comparing simulated results to experimental data. The computer program, developed as a total solution package for migration problems, can be applied not only to multilayer structures made with the same type of plastics but also to structures with different plastics. © 2012 Springer-Verlag.